2022
DOI: 10.1021/acs.jafc.1c06502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exopolysaccharides from Lactiplantibacillus plantarum JLAU103 on Intestinal Immune Response, Oxidative Stress, and Microbial Communities in Cyclophosphamide-Induced Immunosuppressed Mice

Abstract: This study investigated the effects of the exopolysaccharide from Lactiplantibacillus plantarum JLAU103 (EPS103) on the intestinal immune response, oxidative stress, intestinal mucosal barrier, and microbial community in cyclophosphamide-induced immune-suppressed mice. The results showed that EPS103 promoted the secretion of cytokines and the generation of secretory immunoglobulin A and mucin-2 in the small intestine of mice, which might be related to the activation of the MAPK pathway. Additionally, EPS103 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…Short-chain fatty acids (SCFAs), which generated by the degradation and fermentation of indigestible carbohydrates by gut microbiome, could increase intestinal peristalsis and oxygen content in the intestinal mucosa, and promote epithelial cell proliferation and gland development. 82–84 SCFAs, which are important source of energy for immune cells, 85 , 86 are essential substrate of intestinal epithelium normal function, regulation of the immune response and inflammation, 87 , 88 Literature searches suggested that SCFAs were closely associated to UC, 31 , 89 , 90 and the relative levels of bacteria, which could produce SCFAs also changed significantly in UC, which could relieve clinical symptoms and promote intestinal microecological balance, thus playing a positive role in recovery of UC. 91 , 92 Our study found that DSS could lead to significant changes in relative levels of bacteria, such as Lachnospiraceae_NK4A136_group and Muribaculum , which could produce SCFAs in the intestinal tract but different trends after DSS intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs), which generated by the degradation and fermentation of indigestible carbohydrates by gut microbiome, could increase intestinal peristalsis and oxygen content in the intestinal mucosa, and promote epithelial cell proliferation and gland development. 82–84 SCFAs, which are important source of energy for immune cells, 85 , 86 are essential substrate of intestinal epithelium normal function, regulation of the immune response and inflammation, 87 , 88 Literature searches suggested that SCFAs were closely associated to UC, 31 , 89 , 90 and the relative levels of bacteria, which could produce SCFAs also changed significantly in UC, which could relieve clinical symptoms and promote intestinal microecological balance, thus playing a positive role in recovery of UC. 91 , 92 Our study found that DSS could lead to significant changes in relative levels of bacteria, such as Lachnospiraceae_NK4A136_group and Muribaculum , which could produce SCFAs in the intestinal tract but different trends after DSS intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CYC cause dysregulation of intestinal microbiota and impair intestinal immune function in mice. Wang et al [ 46 ] also established an immunosuppressed mouse model using CYC, and found that Lactiplantibacillus plantarum JLAU103 extracellular polysaccharides restored intestinal microbiota disorder caused by CYC, thus regulating intestinal immune response and activating systemic immunity. Our results showed that both medium and high doses of LP had a certain preventive effect on CYC-induced intestinal injury in mice, and the prevention effect of the medium-dose group was the most significant.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Numerous research studies have used Cy to trigger immunosuppression in mouse models. 3,13 Hence, an immunosuppressed mouse model was established using Cy, and the experimental steps are shown in Figure 1A. The BW of mice in each group was observed for 14 d. After 5 days of Cy treatment, the BW (Figure 1B) of mice in all groups, except the NC group, decreased drastically (p < 0.05).…”
Section: Physiological Activities and Immune Organ Indicesmentioning
confidence: 99%